2021
DOI: 10.1038/s41598-021-89964-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation and neuroprotective effects of chlorogenic acids in excitatory synapses of mouse hippocampal slices

Abstract: The increased healthspan afforded by coffee intake provides novel opportunities to identify new therapeutic strategies. Caffeine has been proposed to afford benefits through adenosine A2A receptors, which can control synaptic dysfunction underlying some brain disease. However, decaffeinated coffee and other main components of coffee such as chlorogenic acids, also attenuate brain dysfunction, although it is unknown if they control synaptic function. We now used electrophysiological recordings in mouse hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 92 publications
(113 reference statements)
4
13
0
Order By: Relevance
“…These KA-induced alterations were significantly counteracted by CGA pretreatment, indicating that CGA exerts anti-excitotoxic and neuroprotective effects. Our results are in accordance with those of previous studies, which have investigated the neuroprotective effects of CGA by using in vitro and in vivo experimental models and concluded that CGA protects neurons from glutamate-induced death [ 21 , 24 , 25 , 35 ]. Because the abnormal release of glutamate leading to neuronal loss is a mechanism underlying numerous neurological diseases [ 44 ], inhibiting glutamate release is a key strategy for neuroprotection against excitotoxicity [ 5 , 6 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These KA-induced alterations were significantly counteracted by CGA pretreatment, indicating that CGA exerts anti-excitotoxic and neuroprotective effects. Our results are in accordance with those of previous studies, which have investigated the neuroprotective effects of CGA by using in vitro and in vivo experimental models and concluded that CGA protects neurons from glutamate-induced death [ 21 , 24 , 25 , 35 ]. Because the abnormal release of glutamate leading to neuronal loss is a mechanism underlying numerous neurological diseases [ 44 ], inhibiting glutamate release is a key strategy for neuroprotection against excitotoxicity [ 5 , 6 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…CGA did not affect the basal glutamate release; however, when the synaptosomes were depolarized with 4-AP, CGA inhibited glutamate release, suggesting that CGA reduces the release of glutamate triggered by neuronal activation. This result is consistent with those of electrophysiological studies, which have demonstrated that CGA exerts no significant effects on synaptic transmission or synaptic plasticity under physiological conditions but can mitigate the deterioration of synaptic function in pathological conditions [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…CGA has a variety of biological activities, including anti-inflammatory, analgesic, and neuroprotection activities [ 38 , 39 ]. Previous experiments have shown that CGA can significantly relieve chronic pain by inhibiting GluA1 and affecting synaptic plasticity [ 40 ]. However, the molecular mechanism by which CGA acts on GluA1 remains elusive and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…24 Notably, CGA reduced synaptic dysfunction by increasing synaptic transmission or inhibiting the abnormal transformation of hippocampal plasticity. 25 The CGA intake also prevented cognitive deficits and reduced Aβ plaque deposition via disaggregation of Aβ. 26 Therefore, we hypothesize that gut microbiota and its metabolites may be involved in improving cognitive dysfunction by CGA.…”
Section: ■ Introductionmentioning
confidence: 93%
“…The supplementation of CGA has improved metabolic syndrome, nonalcoholic fatty liver, and type 2 diabetes mellitus. , For example, CGA improved liver lobular inflammation by increasing the percentages of Blautia and Coprococcus in the Firmicutes phylum and improving the plasma SCFA profile in TSOD mice, a spontaneous mouse model of metabolic syndrome . Notably, CGA reduced synaptic dysfunction by increasing synaptic transmission or inhibiting the abnormal transformation of hippocampal plasticity . The CGA intake also prevented cognitive deficits and reduced Aβ plaque deposition via disaggregation of Aβ .…”
Section: Introductionmentioning
confidence: 99%